The Apostles in Early Christian Art and Poetry - Dijkstra, Roald, 1985- (Vigiliae Christianae, Supplements, 2016)
The Apostles in Early Christian Art and Poetry presents the first in-depth analysis of the origins of the representation of the apostles (the twelve disciples and Paul) in verse and image in the late antique Greco-Roman world (250-400). Especially in the West, the apostles are omnipresent, in particular on sarcophagi and in Biblical and martyr poetry. They primarily function as witnesses of Christ's stay on earth, but Peter and Paul are also popular saints of their own. Occasionally, the other apostles come to the fore as individual figures. Direct influence from art on poetry or vice versa appears to be difficult to trace, but principal developments of late antique society are reflected in the representation of the apostles in both media.